TINJAUAN VARIASI TEBAL GROUTING SIKADUR® 31 CF NORMAL Dan PANJANG PENYALURAN TERHADAP DAYA LEKAT BAJA TULANGAN PADA BETON MUTU NORMAL - Anis Rosyidah; Gilang Maulid R; Efendi Yasin (Politeknik Negeri Jakarta, 2011)
Abstract One of the requirements in reinforced concrete structures is the existence of bonding between reinforcement and concrete, so that if the concrete structure of the given load will not slip between reinforcing steel and concrete, with a condition for disbursement length and diameter sufficient reinforcement. This research was conducted with laboratory experimental methods, this study used threaded steel bars 10 mm in diameter grown on cylindrical concrete specimens with a length variation of normal quality distribution of 100 mm and 200 mm, and for thickness variation Sikadur® 31 CF Normal used a thickness variation mm, 2 mm, 3 mm. Each specimen is tested with a method of